(untitled) (Salam International Academic Journal, 2014)
This article is written with the objective to aware young generation of their cultural heritage, to familiarize them with true scholars and personalities among which Imam Abu Hanifa is one of them and correct the misunderstanding about Imam for considering his scholarship in Fiqh only. Therefore, this article tries to study the Imam’s scholarship in Hadith. This first section of the article discusses the Imam as a narrator of Ahadith like the other narrators of the Ahadith. To prove this the quotes of scholars are presented as an evidence to why Imam is considered as narrator of hadith like the others. On the other hand, fourteen conditions set by the Imam to accept any hadith or narration are famous for which he is considered being too strict. Therefore, due to his strictness the ahadith he has narrated are limited. In the other section of the article, the discussion is about Imam who is considered as “Ahlul Jarh wa Tadeel”. Some evidences with examples from the scholars has been presented who considered Imam Abu Hanifa as Ahlul Jarh wa Tadeel. In the third part of the article is about teachers of Imam Abu Hanifa, from whom he acquired knowledge and were known as famous narrators of the Ahadith. This clearly indicates that Imam used to take hadith only from the reliable narrators of Ahadith. In the other part of the article, the discussion is about the musnads (Book of Hadith) and traditions attributed to Iman Abdu Hanifa from which fourteen musnads of Imam are mentioned that were collected by Khuwarizmy named as Musnad of Imam Abdu Hanifa. However, some scholars attribute 21 musnads to Imam Abdu Hanifa. At the end, the article discusses the Ahadith of Iman and whatever traditions that have been collected from him. On the basis of these discussions, confirmation of scholars, his and his student’s books and the deductions from fiqh, it is proved that Iman Abu Hanifa had complete access to Ahadith and has never been alien to hadith narrations.